DETERMINATION OF THE FINAL POSITION OF POSTCOMMUNIST TRANSFORMATIONS: METHODOLOGICAL AND EMPIRIC ASPECTS - Романюк, О.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article is concerned with the pressing and unsolved problem of determining the final position of the postcommunist transformations. Determining the final position is important because it allows you to separate periods of high-quality socio-political change and sustainable development, which have different laws and different logic of development. The author analyzes the problem of the final position in the context of postcommunist development polyvariance.